If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1.2d + -6 = 0 Reorder the terms: -6 + 1.2d = 0 Solving -6 + 1.2d = 0 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 1.2d = 0 + 6 Combine like terms: -6 + 6 = 0 0 + 1.2d = 0 + 6 1.2d = 0 + 6 Combine like terms: 0 + 6 = 6 1.2d = 6 Divide each side by '1.2'. d = 5 Simplifying d = 5
| 18=28+4(-5) | | 4x+7x+8+7x+2=172 | | -5n-5(-8n+3)=13+7n | | -7-4x=2x-7(1-7x) | | 2(5-x)-5x=3-(2+4) | | 5(2)5x=15 | | -5m=4-6m | | -5v-4+7v=-25 | | x+9+12x+7=159 | | -7(7n+5)=-280 | | 6y+3=13y-14 | | 12x-21=100+x | | 41=1+2n | | 2x+6x-7=1 | | 4n+19=6n-5(n+1) | | -18-2a=-9(5a-4) | | 21r=0 | | 12=3x+4*-9 | | -2(8-6r)=36-r | | 78-x=5x | | 1+7x=5+8x | | -5m+20=5(-4m+4) | | 6=-6(a-6)+3(a-5) | | 9=5x-2x | | 4v+5v=18 | | 4(-6x-3)=39-7x | | -9z+8+5=17 | | X^2-2=73 | | 7(1+7a)=a+7 | | -6x-6=6x+6 | | 3(1-8s)=-27 | | 2(4x-2)=3x+6 |